2017
DOI: 10.1177/1934578x1701201217
|View full text |Cite
|
Sign up to set email alerts
|

High Anticancer Properties of Defatted Jatropha Curcus Seed Residue and its Active Compound, Isoamericanol A

Abstract: Jatropha seeds have gained popularity as a biodiesel fuel resource. The process of biodiesel production from the seeds, however, also creates a tremendous amount of defatted residue as a byproduct. In this study, the potential for pharmaceutical usage of extracts from the defatted residue of crushed Jatropha curcus L. seed was examined. Organic and water fractions of both ethyl acetate (EtOAc) and methanol (MeOH) extracts from the seed residue exhibited an inhibitory growth effect on the human cancer cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Although generally considered an invasive species, pokeweed has multiple uses, with various bioactive compounds discovered in diferent pokeweed parts. Neolignans, such as americanin A and isoamericanol A, isolated from pokeweed seeds showed antibreast and colon cancer activities [8][9][10]. Pokeweed storage roots contain triterpenoid saponins that possess useful bioactivities, such as anticancer and antifungal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Although generally considered an invasive species, pokeweed has multiple uses, with various bioactive compounds discovered in diferent pokeweed parts. Neolignans, such as americanin A and isoamericanol A, isolated from pokeweed seeds showed antibreast and colon cancer activities [8][9][10]. Pokeweed storage roots contain triterpenoid saponins that possess useful bioactivities, such as anticancer and antifungal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out on the nutraceutical values of this plant showed the abundant presence of bioactive phytoconstituents like flavonoids (3.69%) and alkaloids (1.89%) and essential minerals such as calcium (5.69%), magnesium (4.22%) and potassium (2.15%) (Arum et al, 2014). Katagi et al (2017) reported that organic and water fractions of EtOAc and MeOH extracts from defatted J. curcas seed residue were effective inhibitors of hepatocellular and breast cancer cell growth. According to Arum et al (2014) and Asep et al (2017), J. tanjorensis and J. gossipifolia are good anticancer plant species.…”
Section: Introductionmentioning
confidence: 99%
“…The lignans, which may have been generated from the oxidative coupling of caffeyl alcohol or caffeic acid, have shown interesting physiological activities. Isoamericanol A has been reported to show neurotrophic activity on rat cells [7], antimelanogenic activity on Melan-a cells [8], anticancer activity on human breast cancer cell lines [9][10][11], as well as plant growth inhibitory activity [12]. Furthermore, isoamericanin A was isolated as a prostaglandin I 2 inducer [13], and (+)-3,3′-bisdemethylpinoresinol has been reported as a metabolite of (+)-sesamin in rat liver homogenate [14,15].…”
Section: Introductionmentioning
confidence: 99%